The ecocidal imagination: dystopian fiction in an era of environmental crisis - Johnson, Hollie (2018)
Specifically addressing the environmental turn of recent dystopian fiction, this thesis investigates the ways in which environmental crisis and climate change have been represented through speculative dystopian futures. This analysis draws on research from both utopian/dystopian studies and ecocritical theory in order to address the lack of dialogue between these two areas, exploring how demands for new approaches to environment and ecology pose challenges to the existing thematic, ideological, and formal conventions of the dystopian genre. Through an analysis of a range of recent dystopian texts, this project explores the ways in which the dystopian novel engages in an ecocritical discourse with contemporaneous environmental policies and cultural conceptions of climate change, highlighting the dialogic relationships between humanity and non-human nature as presented within contexts of extinction, climate change, and environmental exploitation. In particular, this analysis looks at how these novels employ dystopian genre conventions and to what effect, as well as the extent of self-reflexivity within these texts and how this contributes towards an ethical or ideological engagement with contemporary environmental debates.